'All eyes are on you': Gender, race, and opinion writing on the US Courts of Appeals. Issue 3 (30th July 2021) - Moyer, Laura P.; Szmer, John; Haire, Susan; Christensen, Robert K.
Abstract: Because stereotyping affects individual assessments of ability and because of socializing experiences in the law, we argue that women and judges of color, while well‐credentialed, feel pressure to work harder than their white male peers to demonstrate their competence. Using an original dataset of published appellate court opinions from 2008–2016, we find that majority opinions authored by female and non‐white judges go farther to explain and justify their rulings, when compared to opinions written by white male peers. In comparison to other judges, opinions by white men are about 6% shorter, with 11% fewer citations, and 17% fewer extensively discussed citations. Our findings suggest that norms about crafting judicial opinions are gendered and racialized in ways that create higher workloads for women and judges of color.